The SAS in action - Macdonald, Peter (1998)
A comprehensive account of the battles and campaigns, weapons and equipment, training and tactics of Britain's Special Air Service. Included in the text is coverage of the Regiment's wars in the jungles of Malaya and Borneo in the 1950s and 1960s and the Iranian Embassy siege of 1980.